Stabilization of Gambier Process Wastewater and Its Aplication as Silk Dye - Failisnur, Failisnur; Yeni, Gustri (Biopropal Industri, 2013)
Gambier liquid waste is a by-product from gambier (Uncaria gambier Roxb.) processing plant, which is still contains a lot of untapped tannin. This waste could be used for textile dyes, but it is easily damaged during storage. So, the aim of this research is to treat gambier liquid waste so it could be used as silk dye. This research was carried out by concentrating the waste and using stabilizers such as lime (K), alum (T), lotus (F). The parameters tested include pH and fungal growth for up to three months. The results of the process could generate several different colors which is brownish red, brownish yellow and dark green. The waste could save more than 3 months. The color of the waste generated depends on stabilizer type and pH. The use waste on silk produced brownish red color, golden yellow and moss green to dark green.